Effects of weather parameters on endurance running performance: discipline-specific analysis of 1258 races - Mantzios, K.; Ioannou, L. G.; Panagiotaki, Z.; Ziaka, S.; Périard, J. D.; Racinais, S.; Nybo, L.; Flouris, A. D. (Medicine & Science in Sports & Exercise, 2022)
Introduction This study evaluated how single or combinations of weather parameters (temperature, humidity, wind speed, and solar load) affect peak performance during endurance running events and identified which events are most vulnerable to varying weather conditions.